Case Report: The unrelenting journey—successful resolution of catecholaminergic polymorphic ventricular tachycardia (CPVT) through right cardiac sympathetic denervation in a teenager after left cardiac sympathetic denervation - Leung, Hei-To; Kwok, Sit-Yee; Lau, Ming; Lee, Lucius Kwok-Fai; Tsao, Sabrina (Frontiers in Cardiovascular Medicine, 2024)
BackgroundCatecholaminergic polymorphic ventricular tachycardia (CPVT) is a rare inherited arrhythmia disorder characterized by ventricular arrhythmia triggered by adrenergic stimulation.Case presentationA 9-year-old boy presented with convulsions following physical exertion. Bidirectional ventricular tachycardia (VT) during a treadmill test led to the diagnosis of catecholaminergic polymorphic ventricular tachycardia (CPVT). Genetic testing revealed a pathogenic variant of RYR2:c.720G>A (p.ArG2401His). Nadolol was initially started. However, he experienced aborted VT arrest three years later. Flecainide was thus added as dual therapy and he underwent left cardiac sympathetic denervation (LCSD). Subsequently, a transvenous implantable cardioverter-defibrillator (ICD) was implanted because he still had several episodes of bidirectional VT. Despite a good compliance to medication, the patient still had exercise induced VT episodes with new onset of atrial fibrillation. High dose nadolol was required and amiodarone was added. Despite maximizing the dosage of these three antiarrhythmics, the patient continued to experience multiple episodes of ventricular fibrillation with appropriate ICD shocks and persistent atrial arrhythmias. Right cardiac sympathetic denervation (RCSD) was performed as the last modality of treatment. Patient had a total elimination of VT post bilateral sympathectomy. He remained asymptomatic on follow up. A follow-up treadmill test showed no recurrence of exercise-induced PVCs and VT.ConclusionWe illustrated the challenges and the complex decision-making process encountered in managing refractory CPVT. In patients unresponsive to conventional therapies, RCSD in additional to LCSD is a safe and effective alternative treatment. A history of LCSD should not preclude physicians from considering RCSD in children with refractory CPVT.